PERLINDUNGAN HUKUM TERHADAP PERUSAHAAN PASANGAN USAHA YANG BERITIKAD BAIK DALAM PERJANJIAN MODAL VENTURA - Rudyanti Dorotea Tobing (Sekolah Tinggi Ilmu Hukum Tambun Bungai Palangka Raya, 2016)
Formation of Venture Capital Company (PMV) in Indonesia is to finance to SMEs as Partnership Company (PPU). The main function of PMV is equity (equity participation) to the PPU, especially entrepreneurs beginners. Article 1 paragraph 2 of Regulation of the Minister of Finance No. 18 / PMK.010 / 2012 on the Venture Capital Company states that: